Korelasi Tinggi Badan Ibu dengan Panjang Badan Bayi Baru Lahir di Kota Palu - Aspia Lamana; Madarina Julia; Djaswadi Dasuki (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2017)
Background: Body length of newborn babies is related to health in adulthood. Some studies suggested that short people tend to have lower intellectual performance that can reduce working capacity, poor reproductive performance and increase risk of cardiovascular disease and type 2 diabetes. In addition, the less the body’s length of newborns the more adverse long-term health such as obesity, cardiometabolic disorders, and neuro psychiatric conditions were encountered.Objective: To determine the relation of mothers’ height with body length newborns in Palu. Samples are babies born in the first 24-72 hours of private hospitals, health centers, and maternity clinics in Palu. Method: An observational study with cross sectional design. The independent variable is the mothers’ height and the dependent variable is the length of the body of the newborns. Data collection used questionnaires. Data analysis used linear regression.Result and Discussion: There was a correlation between the height of mothers with the body length of newborns (r = 0.26) (p <0.001). There was a significant relationship between mothers’ upper arm circumference, the amount of iron preparations consumed, the height of the father (p <0.001) as well as maternal education (p <0.020) and the sex of the newborn (p <0.015) with the body length of newborns. There was no significant relationship between body length of newborns with socioeconomic status (p <0.861).Conclusion: Mothers’ height is not the main factor affecting the body length of newborns in the city of Palu. Education to newly wed couples and pregnant women about the importance of knowledge that body length of newborns is not only influenced by genetic factors but also by the maternal intake.Keywords: Mothers’ height, newborn body length